The Validity Ethnobotany Book of Claoxylon indicum in the Bukit Tamiang Forest Area, Tanah Laut Regency - Rahmi Murdiyanti; Sri Amintarti; Dharmono Dharmono (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2021)
The people of Kandangan Baru Village have traditional wisdom in utilizing plants. The plants are used as medicine or economic materials. One of them is Claoxylon indicum in the Bukit Tamiang Forest, Tanah Laut Regency which can be used as a value of local wisdom for the local community. The purpose of this study was to describe the validity of the ethnobotany scientific work of Indian geranium as supporting material for ethnobotany. This study uses a development research method with the Educational Design Research (EDR) model and formative evaluation of the Tessmer exam. Teaching materials are in the form of a Popular Scientific Book entitled The Ethnobotany Study of Claoxylon indicum Plants in the Bukit Tamiang Forest Area in the expert test by two validators with a score of 94.4% as well as the practicality of the content for the individual test (one to one) by 3 biology education students of FKIP ULM Banjarmasin who had passed the ethnobotany course had very good results with a score of 3.7.Abstrak Masyarakat Desa Kandangan Baru memiliki kearifan tradisional dalam memanfaatkan tumbuhan. Tumbuhan digunakan sebagai obat atau bahan ekonomi. Salah satunya adalah Claoxylon indicum di Hutan Bukit Tamiang Kabupaten Tanah Laut yang dapat dijadikan sebagai nilai kearifan lokal bagi masyarakat setempat. Tujuan penelitian ini adalah untuk mendeskripsikan validitas karya ilmiah etnobotani geranium India sebagai bahan pendukung etnobotani. Penelitian ini menggunakan metode penelitian pengembangan dengan model Educational Design Research (EDR) dan evaluasi formatif ujian Tessmer. Bahan ajar berupa Buku Ilmiah Populer yang berjudul Kajian Etnobotani Tumbuhan Claoxylon indicum di Kawasan Hutan Bukit Tamiang pada uji pakar oleh dua validator memiliki hasil validasi sangat valid dengan skor 94,4% serta hasil kepraktisan isi untuk uji perorangan (one to one) oleh 3 mahasiswa pendidikan biologi FKIP ULM Banjarmasin yang telah lulus mata kuliah etnobotani memiliki hasil sangat baik dengan skor 3,7.